The Effect of Plant Genotype, Growth Stage, and Mycosphaerella graminicola Strains on the Efficiency and Durability of Wheat-Induced Resistance by Paenibacillus sp. Strain B2 - Samain, Erika; Aussenac, Thierry; Selim, Sameh (Frontiers in Plant Science, 2019)
Plant-growth-promoting rhizobacteria are known as potential biofertilizers and plant-resistance inducers. The current work aims to study the durability of the resistance induced as a response to the inoculation of wheat grains with Paenibacillus sp. strain B2 (PB2) and its influence by plant genotype, growth stage, and Mycosphaerella graminicola strain (the causal agent of Septoria tritici blotch or STB). The results of the plate-counting method showed that PB2 has high potential for wheat-root external colonization (>106 colony-forming unit (CFU)/g of root), and the quantitative real-time polymerase chain reaction (qPCR) analysis demonstrated its internal root-colonization capacity on all tested cultivars. However, the colonization seems to be dependent on wheat-growth stage. The durability of PB2-induced resistance (PB2-IR) was tested at the 3-leaf, tillering, and flag-leaf-growth stages. Additionally, the results showed that the PB2-IR is durable and able to protect the flag leaf, the most important leaf layer during grain fill. It conferred a high protection efficiency (55–94%) against four virulent strains of M. graminicola and over 11 wheat cultivars with different resistance levels to STB. Although, PB2-IR is dependent on M. graminicola strains, wheat genotypes and growth stages, its efficiency, under field conditions, at protecting the last wheat-leaf layers was not an influence. However, it showed 71–79% of protection and reached 81–94% in association with half of the recommended dose of Cherokee® fungicide. This may be explained using laboratory results by its direct impact on M. graminicola strains in these leaf layers and by the indirect reduction of the inoculum coming from leaves infected during the earlier growth stages. Gene expression results showed that PB2-IR is correlated to upregulation of genes involved in defense and cell rescue and a priming effect in the basal defense, jasmonic acid signaling, phenylpropanoids and phytoalexins, and reactive oxygen species gene markers. To conclude, PB2 induces a high and durable resistance against M. graminicola under controlled and field conditions. The PB2-IR is a pathogen strain and is plant-growth-stage and genotype dependent. These results highlight the importance of taking into consideration these factors so as to avoid losing the effectiveness of induced resistance under field conditions.